Intravascular ultrasound of the proximal left anterior descending artery is sufficient to detect early cardiac allograft vasculopathy. Issue 2 (14th December 2017) - Floré, Vincent; Brown, Adam J.; Pettit, Stephen J.; West, Nick E. J.; Lewis, Clive; Parameshwar, Jayan; Hoole, Stephen P.
Abstract: Objective: Cardiac allograft vasculopathy (CAV) can be detected early with intravascular ultrasound (IVUS), but there is limited information on the most efficient imaging protocol. Methods: Coronary angiography and IVUS of the three coronary arteries were performed. Volumetric IVUS analysis was performed, and a Stanford grade determined for each vessel. Results: Eighteen patients were included 18 (range 12‐24) months after transplantation. Angiographic CAV severity ranged from none (CAV0) to mild (CAV1), whereas IVUS CAV severity ranged from none (Stanford grade I) to severe (grade IV). Maximal intimal thickness measured with IVUS was significantly greater in the LAD (0.84 ± 0.48 mm) than in the LCX (0.46 ± 0.32 mm) or the RCA (0.53 ± 0.41 mm, P  = .005). Diagnostic accuracy of IVUS in the left anterior descending artery was 100% (18 of 18 Stanford grades matched the patient's highest overall Stanford grade), 66% in the right coronary artery (12 of 18), and 56% in the left circumflex artery (11 of 18). The minimal required length of left anterior descending artery pullbacks to attain 100% accuracy was 36 mm (range 3‐36 mm) distal from the guide catheter ostium. Conclusions: These data suggest that focal IVUS imaging of the proximal LAD followed by volumetric analysis may suffice when screening for transplant vasculopathy.